The feasibility of decreasing the thresholds for biopsy in Kwak and C TIRADSs - Fu, Chao; Cui, Yiyang; Li, Jing; Wang, Yan; Si, Caifeng; Cui, Kefei (Frontiers in Oncology, 2023)
Objectives To estimate the feasibility of decreasing the original thresholds for biopsy in the Kwak Thyroid Imaging Reporting and Data System (Kwak TIRADS) and Chinese Thyroid Imaging Reporting and Data System (C TIRADS). Methods This retrospective study included 3,201 thyroid nodules from 2,146 patients with a pathological diagnosis. We lowered the original fine-needle aspiration (FNA) thresholds with the TR4a-TR5 in Kwak and C TIRADSs and calculated the ratio of additional benign-to-malignant nodules being biopsied (RABM). If the RABM is less than 1, the decreased FNA thresholds could be accepted and used to the modified TIRADSs (modified C and Kwak TIRADSs). Then, we estimated and compared the diagnostic performance between the modified TIRADS and the original TIRADS to determine if the decreased thresholds could be an effective strategy. Results A total of 1,474 (46.0%) thyroid nodules were diagnosed as malignant after thyroidectomy. The TR4c-TR5 in Kwak TIRADS and TR4b-TR5 in C TIRADS had a rational RABM (RABM < 1). The modified Kwak TIRADS had higher sensitivity, a positive predictive value, a negative predictive value, lower specificity, an unnecessary biopsy rate, and a missed malignancy rate compared with the original Kwak TIRADS (94.1% vs. 42.6%, 59.4% vs. 44.6%, 89.9% vs. 52.8%, 45.0% vs. 54.9%, 40.6% vs. 55.4%, and 10.1% vs. 47.1%, respectively, P < 0.05 for all). Similar trends were seen in the modified C TIRADS versus the original C TIRADS (95.1% vs. 38.7%, 61.7% vs. 47.8%, 92.3% vs. 55.0%, 49.7% vs. 64.0%, 38.3% vs. 52.2%, and 7.7% vs. 44.9%, respectively, P < 0.05 for all). Conclusions The biopsy of all nodules with TR4C-TR5 in the Kwak TIRADS and TR4B-TR5 in the C TIRADS might be an effective strategy. This paper contributes to the contradiction concerning whether to perform FNA for the nodules smaller than 10 mm.